Bismuth Nanoparticle@Carbon Composite Anodes for Ultralong Cycle Life and High‐Rate Sodium‐Ion Batteries. Issue 48 (7th October 2019) - Xiong, Peixun; Bai, Panxing; Li, Ang; Li, Benfang; Cheng, Mingren; Chen, Yiping; Huang, Shuping; Jiang, Qiang; Bu, Xian‐He; Xu, Yunhua
Abstract: Bismuth has emerged as a promising anode material for sodium‐ion batteries (SIBs), owing to its high capacity and suitable operating potential. However, large volume changes during alloying/dealloying processes lead to poor cycling performance. Herein, bismuth nanoparticle@carbon (Bi@C) composite is prepared via a facile annealing method using a commercial coordination compound precursor of bismuth citrate. The composite has a uniform structure with Bi nanoparticles embedded within a carbon framework. The nanosized structure ensures a fast kinetics and efficient alleviation of stress/strain caused by the volume change, and the resilient and conductive carbon matrix provides an interconnected electron transportation pathway. The Bi@C composite delivers outstanding sodium‐storage performance with an ultralong cycle life of 30 000 cycles at a high current density of 8 A g −1 and an excellent rate capability of 71% capacity retention at an ultrahigh current rate of 60 A g −1 . Even at a high mass loading of 11.5 mg cm −2, a stable reversible capacity of 280 mA h g −1 can be obtained after 200 cycles. More importantly, full SIBs by pairing with a Na3 V2 (PO4 )3 cathode demonstrates superior performance. Combining the facile synthesis and the commercial precursor, the exceptional performance makes the Bi@C composite very promising for practical large‐scale applications. Abstract : A Bi nanoparticle@carbon composite is synthesized by a facile heating method from a commercial product of bismuth citrate. Superior sodium storage performance with ultralong cycle life of 30 000 cycles at 8 A g −1 and ultrahigh rate capability of 71% capacity retention at 60 A g −1 are obtained. Full cells by coupling with a well‐developed cathode also deliver impressive capacity and cyclability.